Ambedkar, Gandhi and Patel: the making of India's electoral system - Vundru, Raja Sekhar (New Delhi : Bloomsbury, 2022)
In 1931 Mahatma Gandhi and Dr. B R Ambedkar met in London and clashed on the future of India$1 (Bs electoral system. Later in 1932 when the British announced reserved seats for dalits, Gandhi went on a fast unto death. Ambedkar saved his life by agreeing to the changed terms of representation, which changed the course of electoral system of India.s
Keywords: Abmedkar; Gandhi